Natural and anthropogenic controls on lake water‐level decline and evaporation‐to‐inflow ratio in the conterminous United States. Issue 7 (28th May 2022) - Fergus, C. Emi; Brooks, J. Renée; Kaufmann, Philip R.; Pollard, Amina I.; Mitchell, Richard; Geldhof, G. John; Hill, Ryan A.; Paulsen, Steven G.; Ringold, Paul; Weber, Marc
Abstract: Lake water levels are integral to lake function, but hydrologic changes from land and water management may alter lake fluctuations beyond natural ranges. We constructed a conceptual model of multifaceted drivers of lake water levels and evaporation‐to‐inflow ratio (Evap : Inflow). Using a structural equation modeling framework, we tested our model on (1) a national subset of lakes in the conterminous United States with minimal water management to describe natural drivers of lake hydrology and (2) five ecoregional subsets of lakes to explore regional variation in water management effects. Our model fits the national and ecoregional datasets and explained up to 47% of variation in Evap : Inflow, 38% of vertical water level decline, and 79% of horizontal water level decline (littoral exposure). For lakes with minimal water management, Evap : Inflow was related to lake depth ( β  = −0.31) and surface inflow ( β  = −0.44); vertical decline was related to annual climate (e.g., precipitation β  = −0.18) and water management ( β  = −0.21); and horizontal decline was largely related to vertical decline ( β  = 0.73) and lake morphometry (e.g., depth β  = −0.18). Anthropogenic effects varied by ecoregion and likely reflect differences in regional water management and climate. In the West, water management indicators were related to greater vertical decline ( β  = 0.38), whereas in the Midwest, these indicators were related to more stable and full lake levels ( β  = −0.22) even during drought conditions. National analyses show how human water use interacts with regional climate resulting in contrasting impacts to lake hydrologic variation in the United States.